Analisis Risiko Postur Kerja Dengan Metode Quick Exposure Checklist (QEC) Dan Pendekatan Fisiologi Pada Proses Pembuatan Tahu (Studi Kasus : Tahu APU Klaten) - Widyarti, Yustina, Etika Muslimah ST., MM., MT (2016)
Industrial development over the years to make the high labor demand and lead to a high risk in the work, especially in terms of posture. Wrong posture can lead to complaints it is necessary to study the disease. The research will be carried out at Al-Azhar Peduli Umat (APU) Klaten in Central Java with five operators and three work stations, namely milling, printing and dyeing. The purpose of this study was to determine the risk posture of the work, knowing the energy consumption based on heart rate, provide recommendations for improvement and determine complaints operator. Quick Exposure Checklist (QEC) is used to determine the risk of injury to the musculoskeletal / musculoskeletal system (muscoluskeletal disorder), which focuses on the upper body back, neck, shoulder, and wrist. The energy consumption is obtained from the calculation of pulse before work and after work. Nordic Body Map is a tool to improve the work system and one of the ergonomics checklist questionnaire to determine the body parts of a worker who feels pain before and after doing the work. The results of this research work posture all carriers at risk by a score of QEC, the amount of energy consumption required as well as complaints that dirasaka operator. QEC score of five operators in the amount of 113, 135, 109, 107 and 107 with the action level 3 and level 3 4. Handling of action that further investigation and carried out in the near future while the action level of 4 that further investigation and carried out as soon as possible. Calculation of total energy consumption amounted to 5.188 kcal / min, 1.222 kcal / min, 4,711 Kcal / min, 3.965 kcal / min and 3.965 kcal / min with category level jobs rated moderate, mild and very mild. Complaints of the operator varies in accordance with the limbs used in the work. Suggestions given by researchers is to change the height of the buffer machine, change the position of the bucket and create a buffer collecting bucketout. Keywords: Posture work, QEC, Energy Consumption, Nordic Body Map